Analisa Penyebab Short Cargo terhadap Muatan Soda Ash pada Pelabuhan Java Intergrated Industrial and Port Estate (JIIPE) - Deva Bintang Pratama; Elly Kusumawati; Antony Damanik (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Indonesia is a country located in a strategic area, this makes the shipping sector in Indonesia a very important means of transportation and carrier in the world of international trade and transportation, making loading and unloading services mostly carried out in Indonesia. Therefore, the author conducted research to find out the process of unloading soda ash cargo at JIIPE Port and to find out the causes of short cargo occurring in soda ash cargo at JIIPE Port. This research was carried out with the aim of finding out the process of unloading soda ash at JIIPE port, then to find out the causes of short cargo in the performance of soda ash unloading at JIIPE port. In conducting this research the author used qualitative research methods with techniques in the form of conducting observations, interviews with the staff concerned, and carrying out documentation. From the results of observations, interviews and documentation of findings that the author obtained when conducting research, namely that there was a leak of soda ash cargo in the unloading equipment during soda ash unloading activities at JIIPE port which caused the soda ash cargo to become short cargo from the predetermined manifest. By implementing correct operational standards and using appropriate tools, it is hoped that the process of unloading soda ash can be improved and can minimize short cargo incidents when unloading soda ash. It is hoped that the results of this research will provide insight for loading and unloading companies to reduce losses due to short cargo and can also optimize logistics services at the Java Integrated Industrial and Port Estate port.